Journal of Eastern Mediterranean archaeology and heritage studies. (Pennsylvania State University Press, 2013)
"...devoted to traditional, anthropological, social, and applied archaeologies of the Eastern Mediterranean, ecompassing both prehistoric and historic periods. The journal's geographic range spans three continents and brings together ... the archaeologies of Greece and the Aegean, Anatolia, the Levant, Cyprus, Egypt, and North Africa."